Pengaruh Kompetensi SDM Dan Kompensasi Terhadap Kinerja Pegawai Dengan Produktivitas Kerja Sebagai Variabel Intervening - Achmad Faddlillah; Nugroho Mardi; Woro Utari (Universitas 45 Surabaya, 2024)
Abstract The research results show that: 1) HR competency has a direct and significant positive effect on employee performance as evidenced by the original sample value of 0.280 and p-values of 0.007. 2) HR competency has a direct and significant positive effect on work productivity as evidenced by the original sample value of 0.434 and p-values of 0.000. 3) Compensation has no direct positive and insignificant effect on employee performance as evidenced by the original sample value of 0.101 and p-values of 0.132. 4) Compensation has a significant positive direct effect on work productivity as evidenced by the original sample value of 0.257 and p-values of 0.012. 5) Work productivity has a significant positive direct effect on employee performance as evidenced by the original sample value of 0.660 and p-values of 0.000. 6) HR competency has a significant positive indirect effect on employee performance and work productivity as evidenced by the original sample value of 0.286 and p-values of 0.000. 7) Compensation has a significant positive indirect effect on employee performance and work productivity with a path coefficient value of 0.170 and a p-value of 0.011.